Insani’s Human Resource Management in Transforming Private Islamic Universities in Jambi - Iryani, Eva; Muntholib, Muntholib; As'ad, As'ad; Badarussyamsi, Badarussyamsi (Yayasan Sembilan Pemuda Indonesia, 2023)
The goal of this study is to create a representation of several tertiary institutions that are capable of significant transformations. The findings of this field research: 1) Management policies in preparing Insani’s Human Resources (SDI) for the transformation agenda at IAI Muhammad Azim with a focus on HR readiness policies and academic governance policies. The Governance Policy at IAI YASNI applies the principles of Insani’s Human Resource Management (MSDI), namely: shura, musyarakah, al-ujrah, and obedience to leaders, 2) The process of transformation through the practice of MSDI in Private Higher Education IAIMA and IAI YASNI is divided into the process of administrative transition and the process of building a transformative work culture and MSDI, 3) The dynamics in the Implementation of the Transformation Agenda at Private Higher Education in Jambi province run dynamically and continuously through internalization of transformative values and strategic planning and capacity building of higher education SDI, 4) There are several barriers to IAI Muhammad Azim’s transformation program, including a lack of commitment to the organization, a dearth of qualified human resources (tridharma and education and training), acclimatization to new technologies and cultural norms, and opposition to internal change. The following factors are preventing IAI Yasni from implementing its change agenda: compensation restrictions, sincerity, resistance, and conflict of interest between administrators, 5) The accomplishments of the transformation agenda that IAI Muhammad Azim can produce, specifically: adjustments to a new work culture, adjustments to human resources from an Islamic values perspective, and institutional adjustments. A new integrated digitalization-based work culture, quality-based tridharma education, and the construction of a new work culture based on competence and sincerity are all part of IAI Yasni’s transformation plan, and 6) Kopertais as a facilitator and institution that fosters and has internal performance, namely assisting universities in preparing material for changes in status transfer.